Efficacy and safety of daclatasvir plus pegylated-interferon alfa 2a and ribavirin in previously untreated HCV subjects coinfected with HIV and HCV genotype-1: a Phase III, open-label study - Sulkowski, Mark S.; Fessel, Walford J.; Lazzarin, Adriano; Berenguer, Juan; Zakharova, Natalia; Cheinquer, Hugo; Côté, Pierre; Dieterich, Douglas; Gadano, Adrian; Matthews, Gail; Molina, Jean-Michel; Moreno, Christophe; et al. (Hepatology international, 2017)
Background Daclatasvir (DCV) is a potent, pangenotypic, hepatitis C virus (HCV) non-structural protein 5A inhibitor with low potential for drug interactions with antiretroviral therapy (ART). We evaluated the safety and efficacy of DCV plus peginterferon alfa-2a/ribavirin (PegIFN/RBV) in HIV-1/HCV genotype-1-coinfected patients. Methods AI444043 (NCT01471574), an open-label, Phase III, single-arm, response-guided treatment (RGT) study included 301 patients. They received DCV doses of 30, 60 or 90 mg once daily (depending on concomitant ART), plus weight-based RBV (<75 kg, 1000 mg/day; or ≥75 kg, 1200 mg/day), and once-weekly PegIFN 180 μg, for 24 weeks. If required by RGT, PegIFN/RBV without DCV was extended for an additional 24 weeks of therapy. The primary endpoint was the proportion of patients with sustained virologic response at post-treatment Week 12 (SVR12). Results Overall, 224 (74%) patients achieved SVR12 and the lower bound of the 95% confidence interval was higher than the historic SVR rate with PegIFN/RBV alone (70 vs. 29%). Most common adverse events (AEs) were fatigue, neutropenia, anemia, asthenia and headache. On-treatment serious AEs occurred in 24/301 (8%) patients; 18/301 (6%) discontinued treatment due to AE. Conclusions DCV + PegIFN/RBV led to sustained HCV virologic response in the majority of HIV-1-HCV-coinfected patients, regardless of concomitant ART. HIV control was not compromised and no new safety signals were identified. This study supports DCV use in HIV-1-HCV-coinfected patients, while allowing the vast majority of patients to remain on their existing ART regimen.